A Call for a New Paradigm: Perspectives of Court Personnel and Clinicians on Court-Mandated Treatment Approaches for Domestic Violence Crimes - Barocas, Briana (Journal of family violence, 2024)
Purpose: Despite the emergence of alternative models to traditional Batterer Intervention Programs (BIPs) to address domestic violence (DV), little research has explored stakeholders’ perceptions and experiences of various treatment approaches. Therefore, this study, guided by the stakeholder engagement framework, explored the experiences, attitudes, and beliefs of court personnel and clinicians involved in mandated treatment for those convicted of DV crimes. Method: Two focus groups and nine semi-structured individual interviews were conducted with court personnel and clinicians and were analyzed using an interpretative phenomenological approach. Findings: Five themes emerged: (1) “Capturing a true batterer”: The discrepancy between common perceptions of DV batterers, the legal definition of DV offenses, and the standard treatment approach for DV crimes; (2) A “cookie-cutter” approach: The controversy over the one-size-fits-all approach of court-mandated treatment; (3) “I don’t have the tools”: Professionals’ frustration with policy and practice limitations; (4) The need for more inclusive treatment: Broadening the range of participants involved in the DV treatment process, and (5) A call for a shift in pedagogy: A new paradigm for DV and DV treatment. Overall, various stakeholders (i.e., court personnel and clinicians) expressed a sense of helplessness while attempting to navigate current DV statutes, court-mandated BIPs/DV treatment, and the realities of DV. Conclusion: The narratives of stakeholders point to the desire and the need for a new treatment paradigm to address the various types of DV crimes, the needs of those convicted of misdemeanor DV crimes, and the broader impact of DV.